Dense Cloud Cores revealed by ALMA CO observations in the low metallicity dwarf galaxy WLM. Issue Volume 11:Issue S321(2015) (21st March 2017) - Rubio, M.; Elmegreen, B.; Hunter, D.; Cortes, J.; Brinks, E.; Cigan, P.
Abstract: Understanding stellar birth requires observations of the clouds in which they form. These clouds are dense and self-gravitating, and in all existing observations, they are molecular with H2 the dominant species and CO the best available. When the abundances of carbon and oxygen are low compared to hydrogen, and the opacity from dust is also low, as in primeval galaxies and local dwarf irregular galaxies CO forms slowly and is easily destroyed, so it cannot accumulate inside dense clouds. Then we lose our ability to trace the gas in regions of star formation and we lose critical information on the temperatures, densities, and velocities of the material that collapses. I will report on high resolution observations with ALMA of CO clouds in the local group dwarf irregular galaxy WLM, which has a metallicity that is 13% of the solar value and 50% lower than the previous CO detection threshold and the properties derived of very small dense CO clouds mapped..